Bioleaching of heavy metals from sediment: significance of pH - Chen, SY; Lin, JG (My University, 2001)
Bioleaching process, which causes acidification and solubilization of heavy metals, is one of the promising methods for removing heavy metals from contaminated sediments. The solubilization of heavy metals from contaminated sediments is governed by the sediment pH. In the present study, the significance of pH in bioleaching of heavy metals from contaminated sediment was evaluated at different solid contents of sediments in a bench-scale reactor. Results showed that a temporal change of pH in the bioleaching process was effected by the buffering capacity of the sediment particulates. The variations of pH in this bioleaching process were calculated by a modified logistic model. It was observed that solubilization of heavy metals from sediments is highly pH-dependent. In addition, a non-linear equation for metal solubilization relating pH value in the bioleaching process was established. This allows an easier and faster estimate of metal solubilization by measuring pH in the bioleaching process. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: bioleaching; contaminated sediment; heavy metal; pH; thiobacilli